Does Propulsive Force Asymmetry during Gait Provide Additional Objective Functional Information to Augment the Traditional Assessment of Prosthetic Fit?. Issue 1 (January 2021) - White, Hank; Jacobs, Cale; Augsburger, Sam; Miller, Eric; Walker, Janet; Iwinski, Henry
ABSTRACT: Introduction: A poorly fitting prosthesis can cause pain and result in a less efficient and a less symmetrical gait pattern for children with amputations; however, fit is generally determined by subjective patient reports of discomfort and/or clinical observation when walking. The purpose of this study was to determine if peak propulsive forces during gait provide clinically relevant objective information to augment the traditional prosthesis fit assessment. Materials and Methods: This prospective study compares propulsive force asymmetry with traditional assessments of prosthesis fit. Subjects were between 4 and 21 years of age, with unilateral lower-limb deficiencies, currently wearing the same prosthesis for at least 1 year, and able to walk independently without an assistive device. The absolute asymmetry indexes of peak propulsive forces between the involved and uninvolved limbs were calculated from force data collected from three trials of overground walking at a self-selected velocity. Asymmetry indexes greater than 36.4% were considered clinically meaningful and were associated with poor prosthesis function. A physician and/or a prosthetist, blinded to the results of the gait assessments, then determined the quality of prosthesis fit. Results: Thirty-one subjects (20 males, 11 females; mean age, 13.1 years) participated. The traditional prosthetic fit assessment identified 13 prostheses as properly fitting and 18 as poorly fitting. Peak propulsive force asymmetry exceeded the threshold of 36.4% for 15 subjects and categorized as functioning poorly. The proportion of positive agreement of correct fit and correct function was 71% (κ coefficient = 0.42). Conclusions: Peak propulsive force asymmetries offer clinically meaningful objective functional data to augment the traditional fit assessment.